2005
DOI: 10.1111/j.1439-0396.2005.00566.x
|View full text |Cite
|
Sign up to set email alerts
|

α‐Ketoglutarate (AKG) absorption from pig intestine and plasma pharmacokinetics

Abstract: To study the absorption, metabolism and kinetics, the AKG (in different concentrations) was administered intravenously, intra-portally, orally and directly into the ileum or duodenum of pigs, chronically fitted with portal and jugular catheters and T-shaped cannula at the duodenum and ileum. Additionally, this study was conducted to determine the influence of low pH, Fe(2+) or/and SO on AKG gut absorption and conversely FeSO(4) and FeSO(4)/AKG on Fe(2+) gut absorption. It is concluded that AKG was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…Alpha-ketoglutarate is formed during the Krebs cycle and can also be synthesized by certain anaerobic bacteria, including several species of Bacteriodes (Allison et al 1979). Increased levels have been associated with a number of benefits including: increased bone growth as measured by the length of the 6th rib in pigs (Andersen et al 2008), decreased cholesterol levels in rats (Radzki et al 2009), protection of gut mucosa and kidney function (Dabek et al 2005), and possible prevention of inappropriate muscle catabolism during times of stress, such as surgery, injury and illness (Wiren et al 2002). As with several other observed metabolite differences, the increase in alpha ketoglutarate is likely due to changes in the composition of the intestinal microbe population.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-ketoglutarate is formed during the Krebs cycle and can also be synthesized by certain anaerobic bacteria, including several species of Bacteriodes (Allison et al 1979). Increased levels have been associated with a number of benefits including: increased bone growth as measured by the length of the 6th rib in pigs (Andersen et al 2008), decreased cholesterol levels in rats (Radzki et al 2009), protection of gut mucosa and kidney function (Dabek et al 2005), and possible prevention of inappropriate muscle catabolism during times of stress, such as surgery, injury and illness (Wiren et al 2002). As with several other observed metabolite differences, the increase in alpha ketoglutarate is likely due to changes in the composition of the intestinal microbe population.…”
Section: Discussionmentioning
confidence: 99%
“…Absorption is facilitated through secondary active transporters coupled to the sodium gradient known as the sodium dicarboxylate cotransporters (Pajor, 1999) with the highest rate of absorption in the small intestine followed by the stomach and colon (Buddington et al., 2004). Despite the low portal uptake of AKG and its short systemic half‐life (∼5 min) (Dabek et al., 2005), AKG increases bone mineral density and mechanical strength, when given orally to turkeys (Tatara et al., 2004, 2005a), pigs (Kowalik et al., 2005b) and lambs (Harrison et al., 2004; Tatara et al., 2007). Whilst the question of whether AKG supplements, given postnatally, have a permanent effect on bone mineralisation in pigs has yet to been resolved, a recent study has shown the potential usefulness of AKG treatment in preserving bone mass as well as lowering bone turnover in post‐menopausal women (Tocaj et al., 2003), results which suggest a link between enteral AKG and an increase in oestrogen levels.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that AKG, as well as digestive enzymes, interacts with enterocytes and is involved in amino acid biosynthesis, offering advantages in a catabolic state and thus may also affect the rate of gluconeogenesis in mucosa cells [2,21,34,[36][37][38]. On the other hand, AKG in enterocytes undergoes amination and appears in the plasma as glutamate [36] which may stimulate insulin exocytosis from β-cells in response to glucose stimulation [39].…”
Section: Discussionmentioning
confidence: 99%